Terror in Chechnya : Russia and the Tragedy of Civilians in War. - Gilligan, Emma (Human rights and crimes against humanity., 2009)
Terror in Chechnya is the definitive account of Russian war crimes in Chechnya. Emma Gilligan provides a comprehensive history of the second Chechen conflict of 1999 to 2005, revealing one of the most appalling human rights catastrophes of the modern era--one that has yet to be fully acknowledged by the international community. Drawing upon eyewitness testimony and interviews with refugees and key political and humanitarian figures, Gilligan tells for the first time the full story of the Russian military's systematic use of torture, disappearances, executions, and other punitive tactics agains.